Mammals of protected area "La Poligonal" and neighborhood areas in Tandilia hills, Buenos Aires, Argentina - Velasco, Melina Alicia (2013)
The information about richness and distribution of the mammals that inhabit the highland grasslands of the Tandilia hills is scarce. The main objective of this work was to provide a list of the mammal species that inhabiting the protected area ?La Poligonal? in the Tandilia hills. We report species of confirmed presence and also species of potential presence. We also identified the conservation status of each one. Our results showed a total of 39 mammal species, with 32 native species and seven exotic species. These species represent 35 genera, and are grouped in 17 families and seven orders. The most diverse order was Rodentia represented for 15 species. Two species in Argentina are catalogued as Near Threatened, one is vulnerable and the rest are catalogued as Least Concern. We ho